Viscosity measurement of Xanthan–Poly(vinyl alcohol) mixture and its effect on the mechanical properties of the hydrogel for 3D modeling - Yasutomo Shimizu (Nature Portfolio, 2018)
Abstract Biomodels made of poly(vinyl alcohol) (PVA) are demanded because they can represent the geometries and mechanical properties of human tissues realistically. Injecting and molding, commonly used in three-dimensional (3D) modeling, help to represent the blood vessels accurately. However, these techniques sometimes require higher pressures than the upper pressure limit of the dispensers for pouring in high viscosity materials; the material viscosity should therefore be lower. Moreover, the mechanical properties of the biomodels should be reproduced. This study proposes a PVA solution through the addition of xanthan gum (XG) for 3D modeling, which lowers liquid viscosity while maintaining the mechanical properties of biomodels. XG is known to facilitate the achievement of non-Newtonian fluidity; however, the effects of XG on a PVA solution and PVA hydrogel (PVA-H) are not confirmed. The viscosity measurement using 15 wt% PVA with XG solution (PVA/XG) shows that it will provide easier pouring than 17 wt% PVA solution. The tensile test using the PVA-H of PVA(15 wt%)/XG(0.2 wt%) reveals that the gel is comparable in Young’s modulus to 17 wt% PVA-H. X-ray diffraction shows the crystalline structures of the PVA/XG gel and PVA-H are identical. Thus, this PVA/XG would be useful for fabricating biomodels using injection molding techniques.